2016
DOI: 10.1016/j.ajog.2016.01.193
|View full text |Cite
|
Sign up to set email alerts
|

The placental membrane microbiome is altered among subjects with spontaneous preterm birth with and without chorioamnionitis

Abstract: BACKGROUND Preterm birth (PTB) is a leading cause of neonatal morbidity and mortality and is not uncommonly associated with chorioamnionitis. We recently have demonstrated that the placenta harbors a unique microbiome with similar flora to the oral community. We also have shown an association of these placental microbiota with PTB, history of antenatal infection, and excess maternal weight gain. On the basis of these previous observations, we hypothesized that the placental membranes would retain a microbiome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
241
3
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 248 publications
(270 citation statements)
references
References 67 publications
(98 reference statements)
9
241
3
15
Order By: Relevance
“…Furthermore, whole-genome shotgun sequencing of placental membranes (fetal chorion and/or villous placental membranes) from term deliveries without chorioamnionitis demonstrated the presence of a diverse range of bacteria, including Enterobacter spp., E. coli, Acinetobacter lwoffii, Acinetobacter johnsonii, and Lactobacillus crispatus (120). These findings redefine our understanding of the placental microenvironment and challenge the view that the fetus exists normally within a sterile compartment.…”
Section: Host Defenses and Pathways Of Microbial Invasion Of The Chormentioning
confidence: 46%
See 3 more Smart Citations
“…Furthermore, whole-genome shotgun sequencing of placental membranes (fetal chorion and/or villous placental membranes) from term deliveries without chorioamnionitis demonstrated the presence of a diverse range of bacteria, including Enterobacter spp., E. coli, Acinetobacter lwoffii, Acinetobacter johnsonii, and Lactobacillus crispatus (120). These findings redefine our understanding of the placental microenvironment and challenge the view that the fetus exists normally within a sterile compartment.…”
Section: Host Defenses and Pathways Of Microbial Invasion Of The Chormentioning
confidence: 46%
“…The bacterial pathogens that are most frequently isolated in cases of chorioamnionitis include the human Ureaplasma species (Ureaplasma parvum and Ureaplasma urealyticum), Fusobacterium spp., Streptococcus spp., and, less frequently, Gardnerella spp., Mycoplasma spp., and Bacteroides spp. (1,62,120,(122)(123)(124). Other studies have identified that the sexually transmitted pathogens Chlamydia trachomatis and Neisseria gonorrhoeae, along with the uropathogen E. coli and yeast Candida spp., are also infrequently associated with chorioamnionitis (122,(125)(126)(127)(128).…”
Section: Causative Agents Of Chorioamnionitismentioning
confidence: 99%
See 2 more Smart Citations
“…65,66 However, as aforementioned, the vagina tends to predominately be populated by Lactobacillus species before pregnancy, and tends to be further enriched for Lactobacilli as the pregnancy progresses. [46][47][48] Although Lactobacillus species have been detected in the placental membranes in healthy, term pregnancies by Next-Gen sequencing, 67 the overall diversity of commensal species found within the placental parenchyma, amniotic fluid and neonatal meconium suggest that the vaginal microbiome is unlikely to be the only origin for the full gamut of microbial species found within the intrauterine space. Nevertheless, well-designed animal studies are required to further refine these observations and better define a model of microbial transmission during this period.…”
Section: Impact Of Maternal Nutrition In Pregnancy On Offspring Gut Mmentioning
confidence: 99%